[OP.8D.02] FIRST IN MAN TREATMENT OF SEVERE BP VARIABILITY WITH BAROREFLEX ACTIVATION THERAPY. (September 2016) - Lobo, M.D.; Adeel, M.Y.; Wolff, C.B.; Julu, P.O.; Shah, M.; Collier, D.M.; Saxena, M.; Floyd, C.; Brier, T.; Kapil, V.; Mukhtar, O.; Radunovic, A.; et al.
Abstract : Objective: Profound BP variability (BPV) is a major cause of cardiovascular morbidity and poor quality of life as there are no optimal pharmacological strategies to help patients. We hypothesised that in a patient with baroreflex dysfunction and preserved efferent baroreflex pathway, carotid sinus stimulation may help control BP, BPV and heart rate variability (HRV). Design and method: A 52 year old man was referred with profound HR and BPV. Home SBPs were in a range of 60–250 mmHg and DBPs were 40–130 mmHg and heart rate (HR) of 60–200 bpm (confirmed with ABPM, see Figure) despite multiple medications including felodipine 30 mg daily, terazosin 16 mg daily, doxazosin 8 mg daily, bisoprolol 20 mg daily and butrans patch 17.5 mcg/hr. After extensive multi-disciplinary investigations the diagnosis was progressive central and peripheral dysautonomia consequent upon immune-mediated neuropathy secondary to undifferentiated connective tissue disease with Sjogren's syndrome. It was not possible to improve BP control with use of clonidine patches and he had frequent severe epistaxes due to hypertensive surges and blackouts due to hypotension and was therefore retired from work on medical grounds. Results: Autonomic function tests confirmed widespread dysautonomia with preserved but attenuated vasodepressor response to carotid sinus massage. Baroreflex activation therapy (BAT) was undertaken after numerous in-patient attempts to control BPV pharmacologically had failed. The Barostim Neo® device was implanted with a right carotid sinus electrode in March 2015 and subsequently device settings were reprogrammed on several occasions to optimise BP control. The patient's BP profile improved considerably following BAT but significant hypotensive episodes continued and thus all antihypertensives were stopped with substantial improvement in HR and BP and halving of BPV and concomitant reduction in epistaxes and syncopal episodes. Figure. No caption available. Conclusions: Severe BPV is uncommon and challenging to manage when caused by baroreflex failure. Some antihypertensive drugs can increase BPV and elevate sympathetic tone which could further impair BP control in patients with this diagnosis. Use of BAT in this setting may be of benefit as long as the carotid sinus nerve and vasodepressor component of the baroreflex still function.